152k views
5 votes
What is the solution of 2m=-6n-5 when n=1,2,3

User Sajib Khan
by
4.6k points

1 Answer

1 vote

Answer:


Explanation:

Simplifying

2m + -6n + 5n + 3m = 0


Reorder the terms:

2m + 3m + -6n + 5n = 0


Combine like terms: 2m + 3m = 5m

5m + -6n + 5n = 0


Combine like terms: -6n + 5n = -1n

5m + -1n = 0


Solving

5m + -1n = 0


Solving for variable 'm'.


Move all terms containing m to the left, all other terms to the right.


Add 'n' to each side of the equation.

5m + -1n + n = 0 + n


Combine like terms: -1n + n = 0

5m + 0 = 0 + n

5m = 0 + n

Remove the zero:

5m = n


Divide each side by '5'.

m = 0.2n


Simplifying

m = 0.2n

User Julien TASSIN
by
5.2k points